The effect of supervisors’ ethical leadership on graduate students’ academic procrastination in China: a moderated mediation model - Wu, Wenhao; Kulophas, Dhirapat; Xupravati, Penvara (Frontiers in Education, 2024)
Introduction Academic procrastination is a pervasive challenge among graduate students that undermines their academic excellence and career advancement while compromising the effectiveness and quality of university academic environments. To address this issue, it is crucial to explore its antecedents. This research investigates the impact of supervisors’ ethical leadership on graduate students’ academic procrastination, employing social learning theory to construct a moderated mediation model. Methods A comprehensive dataset was gathered from 338 graduate students using a three-stage time-lagged method, which ensured the robustness of the empirical analysis. The research utilized a moderated mediation model to examine the relations between supervisors’ ethical leadership, graduate students’ followership, academic interests, and academic procrastination. Results The analysis revealed a significant negative effect of supervisors’ ethical leadership on graduate students’ academic procrastination, with this relation mediated by graduate students’ followership. Furthermore, graduate students’ academic interests moderated the relation between followership and academic procrastination, as well as the effect of supervisors’ ethical leadership on academic procrastination through the mediation of followership. Discussion The findings offer valuable insights into the factors shaping graduate students’ academic behaviors and provide practical guidance for enhancing their academic success and fostering positive academic environments in universities.